Shear strength of steel fibrous concrete beams strengthened by CFRP using various techniques. (April 2022) - Ouda, M.A.; Mashrei, M.A.
Abstract: In recent years, carbon fiber-reinforced polymers (CFRP) have been widely used as the strengtheners in reinforced concrete members. This paper is an experimental study on steel fiber-reinforced concrete (SFRC) beam specimens strengthened by CFRP against shear than using externally bound reinforcement (EBR) and externally bound reinforcement on grooves (EBROG). Sixteen concrete beams with dimensions of 110 mm width, 150 mm depth, and 1300 mm length were tested to assess the effect of steel fibers and to evaluate the effects of grooving techniques in terms of improving the shear capacities of SFRC beams strengthened by CFRP. The beams were designed to fail via a shear failure mode. Five volume fractions of steel fibers were used: 0.0%, 0.8%, 1.5%, 1.5%* and 2%. The beams are tested under four-point loading with two values of shear span-to-depth (a/d) ratios, which were 2.2 and 2.85. The results show that the shear strength and the ductility increase with increasing fiber volume fraction, and that the load-carrying capacity of SFRC beams increased by 33% to 68% compared to the load-carrying capacity of the control beam (without steel fibers). Also, the test results show that strengthening beams using CFRP sheets enhanced the strength and stiffness of the tested beam specimens. The increase in the load-carrying capacity of SFRC beam strengthened by CFRP sheet using the EBR method was 79%, while the increase in the load-carrying capacity of SFRC beams strengthened by CFRP sheet using the EBROG method ranged from 89% to 110% compared to the control beam. Furthermore, the results show that the shape of the grooves influenced the capacity and the failure mode of the tested beams. Finally, it may be noted that the grooving method has a significant effect on the load-carrying capacity and failure mode in comparison with the EBR method.